Epidemiology and clinical course of primary biliary cholangitis in the Asia–Pacific region: a systematic review and meta-analysis - Zeng, Na; Duan, Weijia; Chen, Sha; Wu, Shanshan; Ma, Hong; Ou, Xiaojuan; You, Hong; Kong, Yuanyuan; Jia, Jidong (Hepatology international, 2019)
Aims Epidemiological studies on primary biliary cholangitis (PBC) show heterogeneity. The aim of the present study was to synthesize the prevalence, incidence and clinical course of PBC in the Asia–Pacific region. Methods PubMed, Medline, Cochrane library and EMBASE were searched for epidemiology and clinical course of PBC published up to July, 2019. Meta-analysis was conducted on the epidemiology and clinical course (decompensation, hepatocellular carcinoma and death/liver transplantation) of PBC patients. Random-effect model and fixed-effect model were used to evaluate the pooled prevalence, incidence, mortality/liver transplantation and their 95% confidence intervals as appropriate. Subgroup analysis was performed by stratification with gender, pre- and post-UDCA era, sub-region and publication year. Meta-regression was used to examine the heterogeneity. Results Out of 3460 studies, 18 studies from 7 countries/regions were finally included. The overall prevalence of PBC was 118.75 cases per million (95% CI 49.96–187.55) in the Asia–Pacific region, with the high, medium and low prevalence being in Japan and China (191.18 cases per million), New Zealand (99.16 cases per million) and South Korea and Australia (39.09 cases per million), respectively. The incidence of PBC was 8.55 cases per million per year (95% CI 8.05–9.06). The 5-year accumulative incidence of decompensation, HCC and death/liver transplantation in PBC patients was 6.95% (95% CI 2.07–11.83%), 1.54% (95% CI 0.9–2.19%) and 4.02% (95% CI 2.49–5.54%), respectively. Conclusion In the Asia–Pacific region, the prevalence and incidence of PBC are higher than once expected. PBC tends to be diagnosed at older age and has a relatively low incidence of HCC in this region. Graphic abstract